The Mother–Child Relationship during the First Months of Life: Preliminary Considerations in Preterm as Compared with Term Mother–Infant Dyads - Spairani, S.; Pisoni, C.; Ariaudo, G.; Moncecchi, M.; Balottin, U.; Manzoni, Paolo; Tinelli, C.; Gardella, B.; Politi, P.; Tzialla, Chryssoula; Stronati, Mauro; Orcesi, S. (American Journal of Perinatology, 2018)
Introduction From the prognostic perspective, the quality of the mother–child relationship during the first months of life has been variously associated with different factors such as the child's psychomotor/cognitive development and emotional–behavioral disorders.Methods The main aim of this study was to describe, at term age and 3 months of corrected age, the features and the prevalent patterns of the mother–child relationship in a group of 20 mother–preterm infant dyads and to compare them with those of a group of 20 mother–term infant dyads.Results A relatively high rate of inadequate dyadic synchrony was found in our sample of preterms at 40 weeks of gestational age (half of the sample analyzed). The quality of the dyadic relationship and the prevalent patterns of the mother–child relationship were found to differ between the two groups we studied; moreover, the subjects at risk of relational problems remained substantially the same during the first 3 months of life.Discussion These data underline that in preterm children, the first weeks of life, coinciding with their hospitalization, represent a crucial time for establishing a valid dyadic relationship and for considering and planning any preventive interventions; after all, the earlier the risk of relational problems becomes a real possibility, the more likely it is to negatively impact on a child's overall development.
Keywords: mother-child relationship; preterm birth; motherhood